Extraction of Essential Oils from Sweet Orange Leaves (Citrus aurantium) Using the Microwave Hydrodistillation (MHD) Method - Mawardhi Nabilla Putri Agustin; Andreyan Poerwo Negoro; Ditta Kharisma Yolanda Putri; Meta Fitri Rizkiana (JOBC, 2023)
This study aims to utilize sweet lime leaves, which are only waste that has no value, where sweet lime leaves are one of the ingredients that contain essential oils. Apart from the skin, it turns out that this sweet lime leaf can also be extracted using the Microwave Hydrodistillation (MHD) method. This study uses three variables: the F/S ratios used were 0.375 g/mL, 0.5g/mL, and 0.65 g/mL, the powers used were 150 watts, 300 watts, and 450 watts, and the times used were 30, 60, and 90 minutes. The extraction method uses fresh ingredients with a solvent volume of 200 ml. The test carried out is the GC-MS test. The results of the test method and the purpose of this study were to determine the limonene content in the extraction of sweet lime leaves using the MHD method with variations in ratio, power, and time. The optimum yield of essential oils is at a power of 300 W, 90 minutes, and a ratio of 0.625, with a yield of 0.373%. The most significant components produced in the MHD method of extracting citrus leaves were Germacrene D 29.51%, Alpha-Copaene 18.47%, CIS-CAROPHYLNE 15.42%, 9-Eicosene (E) 8.58% and Limonene 5.51%.